The Effect of Classical Theileriosis Treatment on Thyroid Hormone Levels in Cattle Naturally Infected with Theileria annulata - Issi, M.; Gul, Y.; Basbug, O. (Academic Journals Inc, 2011)
The aim of this study is investigated the effect of classical theileriosis treatment on thyroid hormone levels [trliodothyronine (T-3), thyroxine (T-4) and thyrotropin (TSH)] when applied to cattle naturally infected with Theileria annulata. The material of the study encompasses 10 cattle of different races and ages from two strains (male and female) which are diagnosed with theileriosis (patient group) and 10 cattle which are healthy according to clinical examination (control group), a total of 20 cattle. Blood samples of patient group were taken two times as pre-treatment and post-treatment (a month later), the blood samples of the control group were taken once. In haematological examinations, the number of erythrocytes and leukocytes was determined using Thoma lamina; the hematocryte value was determined using the capillary tube and the amount of haemoglobin was determined according to Sahli's method. The free and total T-3, T-4 and TSH concentrations were analyzed in autoanalyzer according to the electrochemiluminescence immunological test (ECLIA) method. It was detected that mean values of free T-3, free T-4, total T-3 and total T-4 of thyroid hormones were significantly lower than the values of the control group in pre-treatment period (p<0.001, p<0.01, p<0.001 and p<0.01, respectively), mean value of the TSH increased (p<0.05). In post-treatment analysis, there was not statistical difference in all thyroid hormones except for total T, concentration. It was established that although there was increase in total T-4 level when compared with pre-treatment values, the difference between control group and the groups was low on the level of p<0.05. Consequently, it was determined that, besides the classical treatment, no additional treatment is required to establish normal thyroid hormone levels, although the thyroid hormones were seen to decrease in cattle infected with T. annulata.
Keywords: Theileria annulata; tropical theileriosis; thyroid hormones; cattle; treatment